Method for repairing and regenerating decommissioned single-crystal nickel-rich ternary positive electrode material and application thereof

CN123018211APending Publication Date: 2026-10-30QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610286219.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

后续热处理中,炭黑和PVDF热分解产生的还原性气氛会进一步破坏层状正极材料的有序结构,增加了单晶材料再生的难度

Benefits of technology

[0016](1)与现有技术相比,本发明提供的修复再生方法首次提出针对退役单晶富镍三元正极材料修复再生的技术,设计了一种LiOH:KNO3:KCL三元熔盐体系。利用低温段首先形成液相环境,其中电离产生的NO3-强氧化剂氧化退役材料表面的岩盐相Ni2+,生成三价镍离子组成的活性层状羟基氧化镍(NiOOH),同步结合LiOH加速锂化反应与结构修复。同步的在高温段晶体再结晶愈合裂纹的过程中,高熔点KCl的加入则显著提升熔盐在高温段的稳定性,抑制挥发并诱导晶体再结晶愈合裂纹,退役正极材料晶体形貌向规则块状转变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018211A_ABST
    Figure CN123018211A_ABST
Patent Text Reader

Abstract

The application discloses a kind of decommissioned single-crystal nickel-rich ternary positive electrode material repair regeneration method and application thereof, the repair regeneration method includes: providing ternary molten salt system, the ternary molten salt system includes lithium salt, nitrate and chloride composite molten salt system;The ternary molten salt system is mixed with decommissioned single-crystal nickel-rich ternary positive electrode material uniformly, first reaction occurs, then heating occurs second reaction, and the single-crystal nickel-rich ternary positive electrode material after repair is obtained.The repair regeneration method provided by the application has the advantages of low cost, high efficiency, etc., the single-crystal nickel-rich ternary positive electrode material repaired has been fully repaired in composition and structure, the appearance is regular, and the electrochemical performance is greatly improved, which can be widely used in lithium battery positive electrode material field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery cathode material repair technology, specifically relating to a method for repairing and regenerating retired single-crystal nickel-rich ternary cathode materials and its application. Background Technology

[0002] With the increasing global demand for electric vehicles, early-installed lithium-ion batteries are gradually reaching the end of their lifespan (capacity decay to below 80%), leading to a year-on-year accumulation of retired battery packs. Traditional recycling strategies, such as pyrometallurgical and hydrometallurgical techniques, are difficult to economically and efficiently recycle high-value retired lithium battery cathode materials, and are accompanied by high energy consumption and secondary environmental pollution problems. Direct regeneration technology, which has emerged in recent years, promises to overcome this bottleneck. This technology aims to preserve the original crystal structure of retired cathode materials, restoring their electrochemical performance by replenishing active lithium and repairing structural defects, thereby achieving the goal of energy-saving and environmentally friendly recycling.

[0003] Direct regeneration technologies mainly include high-temperature solid-phase regeneration, hydrothermal regeneration, eutectic molten salt regeneration, and liquid-phase lithium replenishment regeneration. High-temperature solid-phase regeneration involves mixing retired cathode materials with lithium salts and then sintering at high temperatures to induce a lithiation reaction and restore the structure. The hydrothermal method utilizes heating and pressurization conditions to promote lithium re-intercalation into the material. The eutectic molten salt method uses binary or ternary low-melting-point lithium salts in a liquid phase environment to replenish lithium. Taking lithium nickel cobalt manganese oxide (NCM) ternary cathode materials as an example, during electrochemical cycling, active lithium is lost due to the formation of an electrolyte interphase (SEI) at the positive and negative electrode interfaces, leading to lithium vacancies inside the cathode and exacerbating lithium / nickel antisite defects. This causes an irreversible transformation of the original layered structure into a salt-rock phase structure. Simultaneously, the stress accumulation caused by repeated lithium ion intercalation and deintercalation leads to the formation of microcracks. Traditional solid-phase sintering technology is effective in repairing shallowly failed cathodes, but for deeply failed materials, the high-energy-barrier spinel phase and rock salt phase (such as NiO) formed on the surface hinder lithium ion diffusion, resulting in poor repair effects. Hydrothermal treatment has limited ability to repair materials with numerous microcracks. In contrast, eutectic molten salt methods excel in structural repair, such as the LiOH-LiCO3, LiCl-LiI, and LiOH-LiNO3 systems. Their advantage lies in providing a high-concentration, homogeneous liquid lithium-ion environment, increasing the concentration gradient for lithium-ion diffusion, and significantly enhancing the ion diffusion rate in the liquid phase.

[0004] However, with the increasing demand for long-cycle stability in lithium-ion batteries, the application of monocrystalline cathode materials is becoming increasingly widespread. Compared with polycrystalline materials, monocrystalline cathode materials, lacking grain boundaries, can effectively resist particle breakage in the early stages of cycling, exhibiting excellent structural integrity and cycle stability. However, after deep cycling, the accumulation of anisotropic lattice stress can induce intragranular cracks. This not only disrupts structural continuity and increases polarization, but also exposes new active interfaces, accelerating electrolyte side reactions and harmful phase transitions (such as the transformation from layered to rock salt phases), leading to a sharp decline in performance. Furthermore, its inherently low specific surface area further limits the efficiency of lithiation reactions during post-retirement repair, significantly increasing the difficulty of regeneration.

[0005] Therefore, using a molten salt system with a fast ion diffusion rate for regeneration has advantages. However, existing molten salt systems mostly focus on low-temperature lithium replenishment repair, which is difficult to effectively heal crystal cracks. If high-temperature repair is used for the molten salt system, problems arise such as the easy volatilization of molten salt components and the difficulty in peeling off the cathode material from the crucible after the molten salt cools and solidifies. Moreover, during the high-temperature sintering regeneration process, the grain size of the single crystal material will inevitably grow further, resulting in worse electrochemical performance after regeneration. In addition, the products obtained by the current mainstream technology for separating retired cathode materials from aluminum foil current collectors usually contain a mixture of carbon black and PVDF binder. In subsequent heat treatment, the reducing atmosphere generated by the thermal decomposition of carbon black and PVDF will further destroy the ordered structure of the layered cathode material, increasing the difficulty of single crystal material regeneration.

[0006] Therefore, the technical problem to be solved by this invention is to fill the research gap in the repair and regeneration of retired single-crystal nickel-rich ternary cathode materials, and to provide a low-cost, high-efficiency ternary molten salt system with both oxidizing and thermal stability to achieve the repair and regeneration of retired single-crystal cathode materials. Summary of the Invention

[0007] The main objective of this invention is to provide a method for repairing and regenerating retired single-crystal nickel-rich ternary cathode materials and its application, so as to overcome the defects of the prior art.

[0008] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0009] The first aspect of this invention provides a method for repairing and regenerating decommissioned single-crystal nickel-rich ternary cathode materials, comprising:

[0010] A ternary molten salt system is provided, wherein the ternary molten salt system includes a lithium salt, nitrate and chloride composite molten salt system;

[0011] The ternary molten salt system is mixed evenly with the decommissioned single-crystal nickel-rich ternary cathode material to produce a first reaction, followed by a second reaction at a higher temperature, resulting in the repaired single-crystal nickel-rich ternary cathode material.

[0012] A second aspect of the present invention provides a single-crystal nickel-rich ternary cathode material obtained by the said repair and regeneration method.

[0013] A third aspect of the present invention provides a single-crystal cathode material comprising the aforementioned single-crystal nickel-rich ternary cathode material.

[0014] A fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the above-described single-crystal positive electrode material or the above-described single-crystal nickel-rich ternary positive electrode material.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects:

[0016] (1) Compared with the prior art, the repair and regeneration method provided by this invention is the first to propose a technology for the repair and regeneration of retired single-crystal nickel-rich ternary cathode materials, and designs a LiOH:KNO3:KCL ternary molten salt system. A liquid phase environment is first formed in the low-temperature section, in which NO3 generated by ionization... - Strong oxidants oxidize the Ni rock salt phase on the surface of decommissioned materials 2+ The process generates active layered nickel hydroxyl oxide (NiOOH) composed of trivalent nickel ions, which simultaneously binds to LiOH to accelerate the lithiation reaction and structural repair. Simultaneously, during the high-temperature crystal recrystallization process to heal cracks, the addition of high-melting-point KCl significantly improves the stability of the molten salt at high temperatures, inhibits volatilization, and induces crystal recrystallization to heal cracks, causing the decommissioned cathode material's crystal morphology to transform into a regular blocky structure.

[0017] (2) The repair and regeneration method provided by the present invention can increase the reaction interface and improve the lithiation efficiency; pre-oxidize the nickel oxide of the salt rock phase on the surface of the decommissioned material at a lower temperature to accelerate the occurrence of the lithiation reaction and structural phase transformation; and provide a stable molten salt system for high-temperature crystal growth. It inhibits the abnormal growth of grains during crystal recrystallization and induces the crystal to grow into a block shape through molten salt; ultimately, the regenerated material is fully repaired in terms of composition and structure, and its electrochemical performance is improved due to the exposure of more active crystal faces. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 These are XRD comparison analysis diagrams of different samples in the embodiments and comparative examples of the present invention;

[0020] Figure 2This is a comparison chart of the electrochemical rate performance of different samples in the embodiments and comparative examples of the present invention;

[0021] Figure 3 This is a comparison chart of the electrochemical 1C rate performance of different samples in the embodiments and comparative examples of the present invention after 200 cycles;

[0022] Figure 4 This is a particle size analysis diagram of DR-NCM613 of the present invention;

[0023] Figure 5 This is a SEM image of the DR-NCM613 of the present invention;

[0024] Figure 6 This is a particle size analysis diagram of QS-NCM613 after ball milling according to the present invention;

[0025] Figure 7 This is a SEM image of QS-NCM613 after ball milling according to the present invention;

[0026] Figure 8 This is a particle size analysis diagram of the ball-milled regenerated sample QR-NCM613 of this invention;

[0027] Figure 9 This is a SEM image of the ball-milled regenerated sample QR-NCM613 of this invention;

[0028] Figure 10 This is a particle size analysis diagram of SC-NCM613 of the present invention;

[0029] Figure 11 This is a SEM image of the SC-NCM613 of the present invention;

[0030] Figure 12 This is a SEM image of R2-NCM613 of the present invention;

[0031] Figure 13 This is a SEM image of R1-NCM613 of the present invention;

[0032] Figure 14 This is the thermogravimetric analysis diagram of the ternary molten salt LiOH·H2O:KNO3:KCl of the present invention;

[0033] Figure 15 This is the thermogravimetric analysis diagram of the binary molten salt LiOH·H2O:KNO3 of the present invention. Detailed Implementation

[0034] In view of the problems existing in the prior art, the inventors of this invention have conducted extensive and in-depth research and have provided a method for repairing and regenerating retired single-crystal nickel-rich ternary cathode materials and its application.

[0035] The following will provide a further explanation of the technical solution, its implementation process, and its principles.

[0036] The first aspect of this invention provides a method for repairing and regenerating decommissioned single-crystal nickel-rich ternary cathode materials, comprising:

[0037] A ternary molten salt system is provided, wherein the ternary molten salt system includes a lithium salt, nitrate and chloride composite molten salt system;

[0038] The ternary molten salt system is mixed evenly with the decommissioned single-crystal nickel-rich ternary cathode material to produce a first reaction, followed by a second reaction at a higher temperature, resulting in the repaired single-crystal nickel-rich ternary cathode material.

[0039] Furthermore, the lithium salt includes, but is not limited to, LiOH.

[0040] Furthermore, the nitrates include, but are not limited to, KNO3.

[0041] Furthermore, the chloride includes, but is not limited to, KCl.

[0042] Furthermore, the ternary molten salt system includes the LiOH-KNO3-KCl system.

[0043] In some implementations, the temperature of the first reaction is 450~600°C and the time is 2~3 hours.

[0044] In some implementations, the temperature of the second reaction is 800-850°C and the time is 8-12 hours.

[0045] In some embodiments, the molar ratio of LiOH, KNO3, and KCl in the LiOH-KNO3-KCl system is (3~4):(2~4):(3~4). In this invention, the ternary molten salt system is a molten liquid.

[0046] In some implementations, the ternary molten salt system is liquid, and the decommissioned single-crystal nickel-rich ternary cathode material is solid.

[0047] In some preferred embodiments, the solid-liquid ratio of the decommissioned single-crystal nickel-rich ternary cathode material to the ternary molten salt system is 1 to 2:1. Excessive amounts of the ternary molten salt system will cause an excessive amount of ternary molten salt system to adhere to the crucible, and will also result in a waste of salt usage.

[0048] In some implementations, the decommissioned single-crystal nickel-rich ternary cathode material is ball-milled before repair and regeneration. Since molten salt regeneration leads to further grain growth, excessively large grains can affect the electrochemical performance of the regenerated ternary cathode material. Therefore, ball milling pretreatment is one of the key steps to improve the electrochemical performance of the regenerated ternary cathode material.

[0049] Furthermore, in the ball milling process, the ball-to-material ratio is 10:1, the rotation speed is 200~400r, and the ball milling time is 4~6h.

[0050] Furthermore, the grain size of the decommissioned single-crystal nickel-rich ternary cathode material after the ball milling treatment is <1μm.

[0051] In some implementations, the repair and regeneration method specifically includes: melting the ternary molten salt system to fully coat the ball-milled decommissioned single-crystal nickel-rich ternary cathode material, heating it in an oxygen atmosphere to produce the first reaction, then heating it to produce the second reaction, and cooling it to room temperature to obtain the repaired single-crystal nickel-rich ternary cathode material.

[0052] In some implementations, the repair and regeneration method further includes: mixing the repaired single-crystal nickel-rich ternary cathode material with lithium salt, and then annealing it in an oxygen atmosphere to obtain a pure repaired single-crystal nickel-rich ternary cathode material.

[0053] Furthermore, the lithium salt includes, but is not limited to, any one of LiOH or LiCO3.

[0054] Furthermore, the molar ratio of the repaired single-crystal nickel-rich ternary cathode material to lithium salt is 1:(1.02~1.045).

[0055] Furthermore, the annealing treatment is performed at a temperature of 800~850℃ for 7~10 hours.

[0056] In some more specific implementations, the method for repairing and regenerating decommissioned single-crystal nickel-rich ternary cathode materials specifically includes the following steps:

[0057] (1) Discharged lithium-ion soft-pack batteries are placed in a 7-10% sodium chloride solution for full discharge, and disassembled when the voltage drops below 2.5V.

[0058] (2) The obtained positive electrode material is immersed in a carbonate solution (such as DMC) and the residual electrolyte on the surface is ultrasonically cleaned.

[0059] (3) Soak the positive electrode sheet cleaned in step (2) in 30% phytic acid solution at room temperature for 5~10 minutes, separate the aluminum foil, and obtain black powder.

[0060] (4) Heat-treat the black powder in step (3) at 500℃ for 1~2h in a muffle furnace to remove carbon black and binder PVDF, and obtain pure decommissioned single crystal nickel-rich cathode material active material denoted as S-NCM613.

[0061] (5) The retired single crystal nickel-rich cathode material S-NCM613 obtained in step (4) is milled in a planetary ball mill with a ball-to-material ratio of 10:1, a rotation speed of 350 r, and a milling time of 4~6h, so that the grain size of the retired single crystal nickel-rich cathode material S-NCM613 is reduced to less than 1um, and is denoted as QS-NCM613.

[0062] (6) Mix the ternary molten salt with a molar ratio of LiOH·H2O:KNO3:KCL = (3~4):(2~4):(3~4). Mix the excess ternary molten salt with the ball-milled decommissioned positive electrode active material QS-NCM613 obtained in step (5). After the molten salt melts, it coats the decommissioned QS-NCM613 powder. The decommissioned material QS-NCM613 is solid and the molten salt is liquid. Ensure that the solid-liquid ratio of the crystal growth environment after high-temperature melting is 1~2:1.

[0063] (7) Place the powder mixed in step (6) in a tube furnace and heat it to 450~600℃ in an oxygen atmosphere and hold it for 2~3h so that the lithium salt and potassium nitrate can be fully melted. Then, heat it to 800~850℃ and hold it for 8~12h before naturally cooling it to room temperature to obtain the repaired single crystal nickel-rich ternary cathode material QR-NCM613.

[0064] (8) The repaired single-crystal nickel-rich ternary cathode material QR-NCM613 was placed in deionized water and stirred for 30 min, then ultrasonically assisted for 3 min, and finally centrifuged to obtain the cleaned sample. The sample was placed in a vacuum drying oven at 60 ℃ for 6 h. The liquid generated during the cleaning process was evaporated into deionized water and the molten salt was recovered.

[0065] (9) The dried powder from (8) was mixed with LiOH and placed in a tube furnace (molar ratio 1:1.02~1.045), and sintered in an oxygen atmosphere at 800~850℃ for 7-10h. Annealing was then performed to obtain pure, repaired single-crystal nickel-rich ternary cathode material QR-NCM613. For all heating programs, the heating rate was maintained at 5℃ / min.

[0066] Specifically, in this invention, the reaction mechanism of the first reaction is as follows: a liquid phase environment is first formed in the low-temperature section, wherein NO3 generated by ionization... - Strong oxidants oxidize the Ni rock salt phase on the surface of decommissioned materials 2+ This generates an active layered nickel hydroxyl oxide (NiOOH) composed of trivalent nickel ions, which simultaneously binds to LiOH to accelerate the lithiation reaction and structural repair.

[0067] The reaction mechanism of the second reaction is as follows: during the process of crystal recrystallization and crack healing in the high-temperature section, the addition of high-melting-point KCl significantly improves the stability of molten salt in the high-temperature section, inhibits the volatilization of molten salt and induces crystal recrystallization to heal cracks, and grows into a blocky morphology.

[0068] A second aspect of the present invention provides a single-crystal nickel-rich ternary cathode material obtained by the said repair and regeneration method.

[0069] A third aspect of the present invention provides a single-crystal cathode material comprising the aforementioned single-crystal nickel-rich ternary cathode material.

[0070] A fourth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the above-described single-crystal positive electrode material or the above-described single-crystal nickel-rich ternary positive electrode material.

[0071] Specifically, the lithium-ion battery includes lithium-ion coin cells.

[0072] For example, in this invention, after the repaired monocrystalline nickel-rich ternary cathode material QR-NCM613 is assembled into a coin cell, charge-discharge tests are performed at 25°C and within a voltage range of 2.8~4.3V. Because the repaired monocrystalline nickel-rich ternary cathode material QR-NCM613 has been effectively restored in terms of chemical composition and crystal structure, and because more active crystal faces are exposed, its electrochemical performance is significantly improved.

[0073] In summary, this invention designs a low-cost ternary molten salt system (LiOH-KNO3-KCl) for repairing decommissioned single-crystal ternary Li₂ with a service life exceeding eight years. 1-x Ni 0.6 Co 0.1 Mn 0.3 The O2 (S-NCM613) cathode material fills the research gap in the repair and regeneration technology for retired single-crystal ternary cathode materials, and provides a low-cost and efficient method for repairing and regenerating retired single-crystal materials in a ternary molten salt system.

[0074] For experiments not specifically described in the examples, the procedures or conditions can be performed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available. Other unmentioned raw materials and instruments are all conventionally chosen and do not involve the core technical means of this invention.

[0075] Retired lithium-ion pouch batteries are fully discharged in a 7-10% sodium chloride solution until the voltage drops below 2.5V. The resulting positive electrode material is then immersed in a carbonate solution (such as DMC) and ultrasonically cleaned to remove residual electrolyte. The cleaned positive electrode sheet is then immersed in a 30% phytic acid solution at room temperature for 5-10 minutes. The aluminum foil is then separated to obtain black powder. The black powder is heat-treated in a muffle furnace at 500℃ for 1-2 hours to remove carbon black and the PVDF binder, yielding pure retired positive electrode active material, designated S-NCM613.

[0076] Example 1

[0077] The obtained decommissioned cathode material S-NCM613 was subjected to ball milling in a planetary ball mill at a ball-to-material ratio of 10:1 and a rotation speed of 350 r for 6 hours in both directions. This reduced the grain size of the decommissioned single-crystal cathode material S-NCM613 to below 1 μm, yielding QS-NCM613. Particle size analysis is as follows. Figure 6 As shown, the SEM topography image is as follows: Figure 7 As shown.

[0078] The LiOH·H₂O:KNO₃:KCl molar ratio of 4:2:3 was mixed thoroughly. An excess of this uniformly mixed ternary molten salt was then mixed with ball-milled S-NCM613 (using decommissioned S-NCM613 as a solid and the molten salt as a liquid to ensure a solid-liquid ratio of 2:1 for crystal growth after high-temperature melting). The mixed powder was placed in a tube furnace and heated to 560℃ for 2 hours under an oxygen atmosphere to allow the lithium salt and potassium nitrate to fully melt. The temperature was further increased to 850℃ and held for 10 hours, then naturally cooled to room temperature to obtain the regenerated sample. The regenerated sample was then washed in deionized water with stirring for 30 minutes, followed by ultrasonic-assisted washing for 3 minutes, and finally centrifuged to obtain the cleaned sample. The sample was then dried in a vacuum drying oven at 60℃ for 6 hours. The liquid generated during the washing process was evaporated to deionized water, and the molten salt was recovered. The dried powder was mixed with 4.5% LiOH and placed in a tube furnace for sintering at 850°C in an oxygen atmosphere for 8 hours, followed by annealing to obtain a pure regenerated sample, QR-NCM613. For all heating programs, the heating rate was maintained at 5°C / min.

[0079] X-ray diffraction analysis was performed on the restored sample QR-NCM613, the commercial single-crystal cathode material SC-NCM613, and the decommissioned cathode material S-NCM613 to analyze the degree of crystal structure regeneration. The results are as follows: Figure 1 As shown, the repaired sample QR-NCM613 exhibits the same layered structure as the commercial single-crystal cathode material SC-NCM613. Compared with the deeply decommissioned cathode material S-NCM613, the peaks of the two pairs (006) / (102) and (110) / (108) representing the layered structure are significantly split.

[0080] After the regenerated QR-NCM613 sample was assembled into a coin cell, charge-discharge tests were conducted at 25°C within a voltage range of 2.8–4.3V. The material achieved an initial discharge capacity of 177.6 mAh / g at 0.1C, and discharge capacities of 157.4 mAh / g and 135.3 mAh / g at 1C and 5C rates, respectively. These results significantly outperformed the electrochemical performance of retired cathode material S-NCM613 and also surpassed that of the commercially available cathode material SC-NCM613 of the same type. Figure 2 As shown; it was cycled 200 times at a rate of 1C (1C=160mAh / g), and the results are as follows. Figure 3 As shown, the capacity retention rate reached 84.4%, and the long-cycle retention rate was significantly improved, which is higher than the 56.05% capacity retention rate of the commercial single-crystal cathode material SC-NCM613 after 200 cycles at 1C rate.

[0081] Figure 8 This is a particle size analysis diagram of the regenerated sample QR-NCM613. Figure 9 The image shows the SEM morphology of the repaired and regenerated sample QR-NCM613. The average particle size of the repaired and regenerated sample QR-NCM613 is 0.93 μm, which is smaller than the 1.42 μm of the commercial single-crystal cathode material SC-NCM613. This results in an increase in the lithium-ion migration rate during electrochemical behavior and an improvement in electrochemical performance.

[0082] The mixture of LiOH·H₂O:KNO₃:KCl (4:2:3) was homogeneous, and differential calorimetric analysis (DCA) was performed within the temperature range of 30℃-900℃. The results showed that the ternary molten salt exhibited a thermal weight loss of 33.7%. Figure 14 As shown, the results indicate that, compared to the binary molten salt system, the introduction of high-melting-point KCl can effectively increase the thermal stability of the system.

[0083] Example 2

[0084] The only difference between this embodiment and Embodiment 1 is that the temperature of the first reaction is 450°C and the time is 3 hours. The temperature of the second reaction is 800°C and the time is 12 hours.

[0085] Example 3

[0086] The only difference between this embodiment and Embodiment 1 is that the temperature of the first reaction is 600℃ and the time is 2 hours. The temperature of the second reaction is 830℃ and the time is 10 hours.

[0087] Example 4

[0088] The only difference between this embodiment and Embodiment 1 is that the solid-liquid ratio of the decommissioned single-crystal nickel-rich ternary cathode material to the ternary molten salt system is 1.5:1.

[0089] Example 5

[0090] The only difference between this embodiment and Embodiment 1 is that the solid-liquid ratio of the decommissioned single-crystal nickel-rich ternary cathode material to the ternary molten salt system is 1:1.

[0091] Example 6

[0092] The only difference between this embodiment and Embodiment 1 is that the molar ratio of LiOH·H2O:KNO3:KCL is 3:4:4.

[0093] Example 7

[0094] The only difference between this embodiment and Embodiment 1 is that the molar ratio of LiOH·H2O:KNO3:KCL is 4:3:3.

[0095] Comparative Example 1

[0096] The LiOH·H₂O:KNO₃:KCl molar ratio of 4:2:3 was mixed evenly. This uniformly mixed ternary molten salt was then mixed with unmilled S-NCM613 (using decommissioned S-NCM613 as the solid and the molten salt as the liquid, ensuring a solid-liquid ratio of 2:1 for crystal growth after high-temperature melting). The mixed powder was placed in a tube furnace and heated to 560℃ for 2 hours under an oxygen atmosphere to allow the lithium salt and potassium nitrate to fully melt. The temperature was further increased to 850℃ and held for 10 hours, then naturally cooled to room temperature to obtain the regenerated sample. The regenerated sample was then washed in deionized water with stirring for 30 minutes, followed by ultrasonic-assisted washing for 3 minutes, and finally centrifuged to obtain the cleaned sample. The sample was then dried in a vacuum drying oven at 60℃ for 6 hours. The liquid generated during the washing process was evaporated to deionized water, and the molten salt was recovered. The dried powder was then mixed with a 4.5% molar fraction of... The mixture of LiOH was placed in a tube furnace and sintered at 850°C in an oxygen atmosphere for 8 hours, followed by annealing to obtain a pure regenerated sample, DR-NCM613. For all heating programs, the heating rate was maintained at 5°C / min.

[0097] X-ray diffraction analysis was performed on the repaired sample DR-NCM613, the commercial single-crystal cathode material SC-NCM613, and the decommissioned cathode material to analyze the degree of crystal structure regeneration. The results are as follows: Figure 1 As shown, the repaired samples all exhibit the same layered structure as the commercial single-crystal cathode material SC-NCM613. Compared with the deeply decommissioned cathode material S-NCM613, the peaks of the two pairs (006) / (102) and (110) / (108) representing the layered structure are significantly split.

[0098] After the regenerated DR-NCM613 sample was assembled into a coin cell, charge-discharge tests were conducted at 25°C within a voltage range of 2.8-4.3V. The material achieved an initial discharge capacity of 164.9 mAh / g at 0.1C, and discharge capacities of 141.6 mAh / g and 82.8 mAh / g at 1C and 5C rates, respectively. These performances are significantly higher than the electrochemical performance of the retired cathode material S-NCM613, but slightly lower than that of the commercially available cathode material SC-NCM613 of the same type. The test results are as follows. Figure 2 As shown; it was cycled 200 times at a 1C (1C=160mAh / g) rate, and the test results are as follows. Figure 3As shown, the capacity retention rate reached 52.02%, slightly lower than the 56.05% capacity retention rate of the commercial single-crystal cathode material SC-NCM613 after 200 cycles at 1C. According to... Figure 2 and Figure 3 The results showed that the performance of the repair sample QR-NCM613 was significantly better than that of the repair and regeneration sample DR-NCM613.

[0099] Figure 4 This is the particle size analysis chart of DR-NCM613. Figure 5 This is a SEM image of DR-NCM613. The repaired and regenerated sample has a blocky morphology, but the retired cathode material was not ball-milled to reduce the grain size. During the high-temperature regeneration stage, the crystals grew further, resulting in a grain size increase to 1.73 μm, which is larger than the 1.42 μm of the commercial single-crystal cathode material SC-NCM613. This led to a decrease in the lithium-ion migration rate during electrochemical behavior and a slight decrease in electrochemical performance.

[0100] Comparative Example 2

[0101] The LiOH·H₂O:KNO₃ molar ratio was 4:2. This homogeneous binary molten salt was then mixed with unmilled S-NCM613 (using decommissioned S-NCM613 as the solid and molten salt as the liquid, ensuring a solid-liquid ratio of 2:1 for crystal growth after high-temperature melting). The mixed powder was placed in a tube furnace and heated to 560℃ for 2 hours under an oxygen atmosphere to fully melt the lithium salt with potassium nitrate. The temperature was further increased to 850℃ and held for 10 hours, then naturally cooled to room temperature to obtain the regenerated sample. The regenerated sample was washed in deionized water with stirring for 30 minutes, followed by ultrasonic-assisted washing for 3 minutes, and finally centrifuged to obtain the cleaned sample. The sample was then dried in a vacuum drying oven at 60℃ for 6 hours. The liquid generated during the washing process was evaporated to deionized water, and the molten salt was recovered. The dried powder was then mixed with a 4.5% molar fraction of... The mixture of LiOH was placed in a tube furnace and sintered at 850℃ in an oxygen atmosphere for 8 hours, followed by annealing to obtain a pure regenerated sample R2-NCM613. For all heating programs, the heating rate was maintained at 5℃ / min.

[0102] X-ray diffraction analysis was performed on the repaired sample R2-NCM613, the commercial single-crystal cathode material SC-NCM613, and the decommissioned cathode material to analyze the degree of crystal structure regeneration. The results are as follows: Figure 1 As shown, the repaired samples all exhibit the same layered structure as the commercial single-crystal cathode material SC-NCM613. Compared with the deeply decommissioned cathode material S-NCM613, the peaks of the two pairs (006) / (102) and (110) / (108) representing the layered structure are more clearly split. However, an impurity phase appears at the 16.9° position, which proves that the crystal structure repair is incomplete.

[0103] After the regenerated R2-NCM613 sample was assembled into a coin cell, charge-discharge tests were conducted at 25°C within a voltage range of 2.8-4.3V. The material achieved an initial discharge capacity of 155.7 mAh / g at 0.1C, and discharge capacities of 120.8 mAh / g and 31.1 mAh / g at 1C and 5C rates, respectively. These results are higher than the electrochemical performance of the retired cathode material S-NCM613, but lower than that of the commercially available cathode material SC-NCM613 of the same type. Figure 2 As shown; it was cycled 200 times at a rate of 1C (1C=160mAh / g), and the results are as follows. Figure 3 As shown, the capacity retention rate was 25.0%, indicating that the repaired sample was difficult to cycle for extended periods at 1C. According to... Figure 2 and Figure 3 The results showed that the performance of the repair sample QR-NCM613 was significantly better than that of the repair and regeneration sample R2-NCM613.

[0104] like Figure 12 As shown, the repaired and regenerated sample has an irregular morphology, with a large number of residual coffee rings on the crystal surface due to the rapid volatilization of molten salt, and the particle size grows to 2-3 μm, ultimately resulting in poor electrochemical performance.

[0105] The ternary molten salt was uniformly mixed with LiOH·H₂O and KNO₃ in a ratio of 4:2, and differential calorimetry (DLC) was used for thermogravimetric analysis within a temperature range of 30℃ to 900℃. The results showed that the thermogravimetric loss of this ternary molten salt was 71.52%, as shown in the figure below. Figure 15 As shown.

[0106] Comparative Example 3

[0107] Excess LiOH·H2O was mixed with unmilled S-NCM613 at a molar ratio of 1.1:1 (using decommissioned S-NCM613 as solid and molten salt as liquid to ensure a solid-liquid ratio of 2:1 for crystal growth after high-temperature melting). The mixed powder was placed in a tube furnace and heated to 560℃ for 2 hours under an oxygen atmosphere to allow the lithium salt and potassium nitrate to fully melt. The temperature was further increased to 850℃ and held for 10 hours, then naturally cooled to room temperature to obtain the regenerated sample. The regenerated sample R-NCM613 was placed in deionized water and stirred for 30 minutes, followed by ultrasonic-assisted cleaning for 3 minutes. Finally, it was centrifuged to obtain the cleaned sample. The sample was placed in a vacuum drying oven at 60℃ for 6 hours. The liquid generated during the cleaning process was evaporated to deionized water, and the molten salt was recovered. The dried powder was then mixed with a 4.5% molar fraction of... The mixture of LiOH was placed in a tube furnace and sintered at 850°C in an oxygen atmosphere for 8 hours, followed by annealing to obtain a pure regenerated sample R1-NCM613. For all heating programs, the heating rate was maintained at 5°C / min.

[0108] X-ray diffraction analysis was performed on the repaired sample R1-NCM613, the commercial single-crystal cathode material SC-NCM613, and the decommissioned cathode material to analyze the degree of crystal structure regeneration. The results are as follows: Figure 1 As shown, the repaired samples all exhibited the same layered structure as the commercial single-crystal cathode material SC-NCM613. Compared with the deeply decommissioned cathode material S-NCM613, the peaks of the two pairs (006) / (102) and (110) / (108) representing the layered structure were more clearly split. However, an impurity phase appeared at the 16.9° position, and the content of the impurity phase was higher than that of the control group 1, which proved that the crystal structure repair was less complete.

[0109] After the regenerated sample R1-NCM613 was assembled into a coin cell, charge-discharge tests were conducted at 25°C within a voltage range of 2.8-4.3V. The material achieved an initial discharge capacity of 148.8 mAh / g at 0.1C, and discharge capacities of 99.7 mAh / g and 50.4 mAh / g at 1C and 5C rates, respectively. These results are higher than the electrochemical performance of the retired cathode material S-NCM613, but lower than that of the commercially available cathode material SC-NCM613 of the same type. Figure 2 As shown; it was cycled 200 times at a rate of 1C (1C=160mAh / g), and the results are as follows. Figure 3 As shown, the capacity retention rate was 17.6%, indicating that the repaired sample was difficult to cycle for extended periods at 1C. According to... Figure 2 and Figure 3 The results showed that the performance of the repair sample QR-NCM613 was significantly better than that of the repair and regeneration sample R1-NCM613.

[0110] like Figure 13 As shown, the repaired and regenerated sample has an irregular morphology. The crystal surface also has a large number of residual coffee rings due to the rapid volatilization of molten salt, and there is adhesion between the grains. The grains grow to 2-3 μm, which ultimately leads to poor electrochemical performance.

[0111] Comparative Example 4

[0112] After assembling commercially purchased monocrystalline SC-NCM613 into coin cells, charge-discharge tests were conducted at 25°C within a voltage range of 2.8–4.3V. The material achieved an initial discharge capacity of 177.5 mAh / g at 0.1C, and discharge capacities of 134.3 mAh / g and 75.3 mAh / g at 1C and 5C rates, respectively. The results are as follows... Figure 2 As shown in the figure. After 200 cycles at 1C (1C = 180 mAh / g), the capacity retention reached 60.2%, as shown in the figure. Figure 3 As shown, the electrochemical performance of the above samples is lower than that of the regenerated QR-NCM613 material. Figure 10 This is the particle size analysis diagram of SC-NCM613; Figure 11 This is a SEM image of SC-NCM613.

[0113] All aspects, embodiments, features, and examples of this invention should be considered illustrative in all respects and are not intended to limit the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention.

[0114] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0115] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this invention is not intended to be limited to the specific embodiments disclosed for carrying out the invention, but rather is intended to encompass all embodiments falling within the scope of the appended claims. Moreover, unless specifically stated otherwise, any use of the terms first, second, etc., does not indicate any order or importance, but is used to distinguish one element from another.

Claims

1. A method for repairing and regenerating decommissioned single-crystal nickel-rich ternary cathode materials, characterized in that, include: A ternary molten salt system is provided, wherein the ternary molten salt system includes a lithium salt, nitrate and chloride composite molten salt system; The ternary molten salt system is mixed evenly with the decommissioned single-crystal nickel-rich ternary cathode material to produce a first reaction, followed by a second reaction at a higher temperature, resulting in the repaired single-crystal nickel-rich ternary cathode material.

2. The repair and regeneration method according to claim 1, characterized in that: The lithium salt includes LiOH; And / or, the nitrate includes KNO3; And / or, the chloride includes KCl; Preferably, the ternary molten salt system includes the LiOH-KNO3-KCl system.

3. The repair and regeneration method according to claim 2, characterized in that: The temperature of the first reaction is 450~600℃, and the time is 2~3h; And / or, the temperature of the second reaction is 800~850℃, and the time is 8~12h; And / or, the molar ratio of LiOH, KNO3 and KCl in the LiOH-KNO3-KCl system is (3~4):(2~4):(3~4); And / or, the ternary molten salt system is liquid, and the decommissioned single-crystal nickel-rich ternary cathode material is solid; Preferably, the solid-liquid ratio of the retired single-crystal nickel-rich ternary cathode material to the ternary molten salt system is 1~2:

1.

4. The repair and regeneration method according to claim 2, characterized in that, The retired single-crystal nickel-rich ternary cathode material was ball-milled before being repaired and regenerated. Preferably, the ball milling process takes 4 to 6 hours; Preferably, the grain size of the decommissioned single-crystal nickel-rich ternary cathode material after ball milling is <1μm.

5. The repair and regeneration method according to claim 4, characterized in that, Specifically, it includes: The ternary molten salt system is melted to fully coat the ball-milled decommissioned single-crystal nickel-rich ternary cathode material. The first reaction occurs under an oxygen atmosphere, followed by a second reaction. The material is then cooled to room temperature to obtain the repaired single-crystal nickel-rich ternary cathode material.

6. The repair and regeneration method according to claim 4, characterized in that, Also includes: The repaired single-crystal nickel-rich ternary cathode material was mixed with lithium salt and then annealed in an oxygen atmosphere to obtain a pure repaired single-crystal nickel-rich ternary cathode material. Preferably, the lithium salt comprises LiOH or LiCO3; Preferably, the molar ratio of the repaired single-crystal nickel-rich ternary cathode material to lithium salt is 1:(1.02~1.045). Preferably, the annealing treatment is performed at a temperature of 800~850℃ for 7~10 hours.

7. The single-crystal nickel-rich ternary cathode material obtained by the repair and regeneration method according to any one of claims 1-6.

8. A single-crystal cathode material, characterized in that, Including the single-crystal nickel-rich ternary cathode material as described in claim 7.

9. A lithium-ion battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The cathode material includes the single-crystal cathode material of claim 8 or the single-crystal nickel-rich ternary cathode material of claim 7.

10. The lithium-ion battery according to claim 9, characterized in that: The lithium-ion battery includes lithium-ion button cells.